Fostering Teachers’ Competence of the Integrated STEM Education - Thuy, Nguyen Thi Thu; Bien, Nguyen Van; Quy, Duong Xuan (Jurnal Penelitian dan Pembelajaran IPA, 2020)
For the successful implementation of integrated STEM education, teachers’ competence could be a key element. The purpose of this research is to identify necessary behaviors of competence for teachers’ teaching integrated STEM subjects more efficiently and their desire for professional development courses. The qualitative analysis was utilized to examine teachers’ competence and perceptions of effective STEM teacher professional developments (TPD). Semi-structure interview method with 15 teachers and survey method with 187 teachers were utilized to address our research questions in Vietnam. We found that teachers’ competence in integrated STEM education consists of four components namely, awareness, designing, implementing, assessing and adjusting the STEM teaching plan. Based on the research results, we propose an essential structural model of teachers’ competence to develop professional competence about integrated STEM education and some orientation for building the structure of the professional development program. Implications for effective STEM TPD were documented